Uniform Chitosan Microparticles Prepared by a Novel Spray-Drying Technique. (13th October 2010) - Liu, Wenjie; Wu, Winston Duo; Selomulya, Cordelia; Chen, Xiao Dong
Abstract : Particle size and morphology are important properties of pharmaceutical particles. Preparation of microparticles with uniform particle size and morphology is necessary in order to systematically relate these properties to the release behavior and other functionalities such as drug encapsulation and dissolution. In this study, we successfully prepared monodisperse, nonagglomerated chitosan microparticles in a single step by a novel spray-drying technique. The control of particle size and morphology of spray-dried microparticles was investigated experimentally. Microparticles with larger particle size can be produced when chitosan precursor of higher concentration was used. Storage time of chitosan precursor, drying temperature, and addition of lactose were shown to be crucial parameters that affect the particle morphology. Appropriate choice of the drying temperature and precursor storage time permitted control of the particle morphology, ranging from nearly spherical to cap-shaped. Surface characteristics of the particles can be finely tuned by the amount of lactose added into the chitosan precursor.